2015
DOI: 10.1007/s00384-015-2124-y
|View full text |Cite
|
Sign up to set email alerts
|

Acute appendicitis revealing salpingiosis

Adriana Handra-Luca

Abstract: Dear Editor:We have read with great interest the recent article on histopathological findings in 24,697 cases [1]. Microscopic examination revealed in 7.38 % of the patients unsuspected findings among which endometriosis. Less frequently, remnants of salpingiosis type may also be identified in the appendix, three such cases being reported, to our knowledge, to date [2][3][4]. We have recently seen an additional case of salpingiosis of the vermiform appendix diagnosed incidentally in a previously unreported con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Previous studies have reported endosalpingiosis involving the peritoneum, pelvic organs, retroperitoneum, skin, spinal nerve root attachment, axillary lymph nodes, and the appendix [ 3–7 ]. Most cases of appendiceal endosalpingiosis reported are in a benign appendix; to date, there is only one case report of endosalpingiosis in acute appendicitis, without perforation [ 8 ]. Here we report a case of perforated appendicitis with endosalpingiosis.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported endosalpingiosis involving the peritoneum, pelvic organs, retroperitoneum, skin, spinal nerve root attachment, axillary lymph nodes, and the appendix [ 3–7 ]. Most cases of appendiceal endosalpingiosis reported are in a benign appendix; to date, there is only one case report of endosalpingiosis in acute appendicitis, without perforation [ 8 ]. Here we report a case of perforated appendicitis with endosalpingiosis.…”
Section: Introductionmentioning
confidence: 99%